LITERATURE OF REVIEW EFFECT OF PROFITABILITY, DEBT TO EQUITY RATION AND CURRENT RATIO ON SHARE RETURN (STUDY ON COMPANIES LISTED ON LQ45 PERIOD 2018-2022) - Maya Tika Zulkarnain (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research aims to examine the influence ofprofitability, debt to equity ratio & current ratio onshare return. This research was conducted atcompanies listed on LQ 45 for the 2018-2022 period.This research will use 10 companies using secondarydata with quantitative methods. This research willtest the data with the SPSS 26 statistical tool bytesting the feasibility of the model and hypothesis.